HUBUNGAN KEPATUHAN MENJALANI HEMODIALISA DENGAN QUALITY OF LIFE PADA PASIEN GAGAL GINJAL KRONIK DI RUMAH SAKIT AMINAH TANGERANG - Nursaid Nursaid; Lam Murni Sagala (Indonesian Trust Nursing Journal, 2023)
Chronic Kidney Disease (CKD) patients with Glomerular Filtration Rate (GFR) < 15 ml/min/1.73m2 should undergo renal replacement therapy, one of which is hemodialysis. Compliance with hemodialysis is needed to achieve success in treatment so that it can support the patient's quality of life. The decrease in the quality of life of CKD patient is caused by changes in health during hemodialysis. This study aims to determine the relationship between compliance with hemodialysis and quality of life in patients with chronic kidney failure at Aminah Hospital Tangerang. The population of this study were all CKD’s patients undergoing hemodialysis at Aminah Hospital Tangerang with a total sample of 42 samples taken using purposive sampling technique. The research method used is correlation research with a cross sectional approach and data analysis using the Spearman rank test. From the results of the analysis of the Spearman rank test, the results obtained from the value of Sign. = 0.042 < = 0.05, which means that there is a relationship between adherence to hemodialysis therapy and quality of life in patients with chronic kidney failure at Aminah Hospital Tangerang. The results of this study are expected to be a reference in developing knowledge and understanding of hemodialysis treatments. Abstrak Pasien Chronic Kidney Disease (CKD) dengan tingkat Laju Filtrasi Glomerular (LFG) < 15 ml/menit/1,73m2 harus melakukan terapi pengganti ginjal, salah satunya hemodialisa. Kepatuhan menjalani hemodialisa diperlukan untuk mencapai keberhasilan dalam pengobatan sehingga dapat menunjang quality of life pasien. Penurunan quality of life pasien CKD disebabkan karena perubahan kesehatan selama menjalani hemodialisa. Penelitian ini bertujuan untuk mengatahui Hubungan Kepatuhan Menjalani Hemodialisa Dengan Quality of Life Pada Pasien Gagal Ginjal Kronik Di Rumah Sakit Aminah Tangerang. Populasi penelitian ini adalah semua pasien CKD yang menjalani hemodialisa di Rumah Sakit Aminah Tangerang dengan jumlah sampel sebanyak 42 sampel yang diambil dengan menggunakan teknik purposive sampling. Metode Penelitian yang digunakan yaitu penelitian korelasi dengan pendekatan cross sectional dan analisa data menggunakan uji rank Spearman. Dari hasil analisa uji rank Spearman diperoleh hasil nilai dari Sign. = 0,042 < α = 0,05, yang berarti bahwa ada hubungan antara kepatuhan menajalani terapi hemodialisa dengan quality of life pada pasien gagal ginjal kronik di Rumah Sakit Aminah Tangerang. Hasil penelitian ini diharapkan menjadi referensi dalam mengembangkan pengetahuan dan pemahaman mengenai perawatan hemodialisa